The Role of Information Technology in Managing Employee Diversity and Improving Company Performance - Septian Renaldi Dowongi; Raditya Eka Putra Tahir; Hayden Rafael Rainhard Moniaga; Michael Steve Mamengko; Christo Richard Walelang; Wulan Melani Christy Ngion (Jurnal Syntax Admiration, 2025)
Workforce diversity in modern companies presents challenges in management and communication that can impact organizational performance. Information technology plays a crucial role in managing diversity by enhancing operational efficiency and creating an inclusive work environment. This study aims to empirically examine the influence of information technology on employee diversity and its impact on company performance.This research employs a descriptive method with a qualitative approach, with data collection conducted through a literature review of scientific journals, academic articles, and relevant research reports. The findings indicate that the optimal implementation of information technology can maximize human resource potential, improve communication effectiveness, reduce discrimination, and foster innovation within companies. Additionally, the applied management information systems facilitate performance evaluation based on transparent and objective data. The conclusion of this study suggests that companies adopting information technology in managing workforce diversity can achieve increased productivity and a competitive advantage in the digital era.